ADAPTASI PENDIDIKAN ERA 4.0: COVID-19 MOMENTUM MENGKONSTRUKSI SISTEM PENDIDIKAN DI INDONESIA - Maharani, Adinda; Putra, Rahmat Hardian (Universitas Negeri Malang, 2023)
ADAPTATION TO EDUCATION ERA 4.0: COVID-19 MOMENTUM FORCONSTRUCTING THE EDUCATION SYSTEM IN INDONESIA The world of education has become one of the sectors created due to the COVID-19 pandemic,ranging from basic education to higher education. This situation causes a digital-based distancelearning system by utilizing advanced technology. This is certainly one of the right moments forthe implementation of education in the 4.0 era. However, what is interesting is that when theCOVID-19 pandemic situation began to develop, various online courses provided by variouseducational institutions and communities aimed at improving their life skills. Of course, thisbecomes interesting because of the construction of the education system in Indonesia whichfocuses more on the cognitive aspect alone. This study uses a literature review by analyzing theconstruction of the education system in Indonesia with the adaptation of education in the 4.0 era.The research findings show that the phenomenon of the development of the education systemand the education community shows a significant increase in interest. The online program is aform of training and support for young people to continue to develop their skills and mindset ashigh as possible so that they can build their confidence and potential. It can be said that theconstruction of education by directing the need to increase life skills will become a form ofcommunity development effort. Dunia pendidikan menjadi salah satu sektor yang terdampak karena adanya pandemi COVID-19,mulai dari pendidikan dasar hingga level perguruan tinggi. Situasi ini menyebabkan sistempembelajaran dituntut melaksanakan pembelajaran jarak jauh berbasis digital denganmemanfaatkan kecanggihan teknologi. Hal ini tentu menjadi salah satu momentum adaptasiterlaksananya pendidikan di era 4.0. Namun, yang menarik adalah saat pandemi COVID-19 inibanyak berkembang berbagai kursus online yang disediakan berbagai institusi maupunkomunitas pendidikan yang bertujuan untuk meningkatkan life skill mereka. Tentu ini menjadimenarik karena adanya konstruksi mengenai sistem pendidikan di Indonesia yang lebihmenekankan aspek kognitif semata. Penelitian ini menggunakan kajian literatur denganmenganalisis konstruksi sistem pendidikan di Indonesia dikaitkan dengan adaptasi pendidikanera 4.0. Temuan penelitian menunjukkan bahwa, fenomena berkembangnya kursus onlinebanyak diselenggarakan institusi pendidikan maupun komunitas pendidikan menunjukkanpeningkatan minat yang signifikan. Program kursus online menjadi bentuk pelatihan dan upayadukungan bagi para generasi muda untuk terus mengembangkan keterampilan dan pola pikirmereka ke tingkat setinggi mungkin sehingga mereka dapat membangun kepercayaan diri dan potensi mereka. Dapat disimpulkan bahwa adanya konstruksi pendidikan dengan mengarahkanpada peningkatan kebutuhan akan peningkatan life skill menjadi bentuk upaya pembangunanmasyarakat.